KINERJA BADAN PENGAWAS PEMILU KOTA BATAM DALAM PENANGANAN PELANGGARAN PEMILU SERENTAK TAHUN 2019 DI KOTA BATAM - Limbong, Anita Sakdiah; Lodan, Karol Teovani (LPPM Universitas Putera Batam, 2021)
Concurrent elections are a means of implementing the sovereignty of the people to vote for the executive and legislative elections held jointly on the same day, date, time. However, in practice, there is an election violation which is an act that violates the Electoral Law, this is the responsibility of the Election Supervisory Board. Then the purpose of the researchers is to describe and analyze the Performance of Batam City Election Supervisory Board in Handling Simultaneous Election Violations in 2019 In Batam City. The research method used is qualitative descriptive The results of this study show that the Performance of Batam City Election Supervisory Board in Handling Simultaneous Election Violations in 2019 In Batam City is categorized well by using productivity indicators Productivity, Responsiveness, Responsiveness and accountability indicators, but in Bawaslu performance service quality indicators are not maximal due to the fact that there are still people who do not receive information. So the advice that researchers can give is to provide regular updates of information on the website or information system Bawaslu Batam City and the scope of information provided contains about the findings of alleged election violations, reports of alleged election violations, formil, material requirements for public education.